The Birth of Spontaneously Conceived Quintuplets: Case Report - Pak, Song Bong; Kye, Chun Yong; Pak, Song Suk; Ham, Sun Hui; Ji, Mi Gyong; Ri, Jong Nam (Medical Science Journal for Advance Research, 2026)
Background: The birth of quintuplets is rarely reported in the world. Assisted reproductive technologies have contributed significantly to increase in the incidence of multiple pregnancies. In multiple pregnancy the risk of perinatal morbidity and mortality is high and often linked to prematurity. Case Report: A 28-year-old woman, gravida 1 para 0, referred to Pyongyang Maternity Hospital on the diagnosis of multiple pregnancy with 3 or more babies at 30 weeks and 5 days of gestation. At admission she was diagnosed as gestational hypertension, obesity and multiple pregnancy. The live quintuplets were born by Cesarean Section at 32 weeks of gestation. All the quintuplets survived through the intensive and recovery care for 140 days and discharged in good health. Discussion: The early diagnosis of multiple pregnancy and regular checkup according to the high-risk pregnant women care system are effective.